Strategi Pengembangan Usaha Mikro Kecil dan Menengah Petta Coffee di Desa Soni Kecamatan Dampal Selatan Kabupaten Tolitoli - Moh Nasir Hi Hasan Dg Marumu; Sulwan; Ilham (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are productive businesses run by individuals or groups aimed at improving their welfare. The presence of MSMEs in villages is seen as having the potential to develop the community's economy. A coffee shop is a business that serves beverages such as coffee and tea, as well as snacks such as fried foods and cakes. Coffee shops are often known as warung kopi or warkop.